Experimental studies on seismic behavior of precast hybrid steel–concrete beam. Issue 3 (February 2019) - Zhang, Xizhi; Zhang, Shaohua; Niu, Sixin
This study aims to investigate the seismic behavior of precast hybrid steel–concrete beams. Five full-scale beam specimens, including four precast hybrid steel–concrete beams and a conventional precast concrete beam, were tested under cyclic loading. Furthermore, a new connection form was proposed to facilitate the constructability of the steel-to-concrete connection. The main experimental parameters were the steel beam length and the longitudinal reinforcement ratio. In addition, the influence of the reduced beam section of the steel beam on seismic behavior of precast hybrid steel–concrete beams was observed and investigated. Detailed analysis was performed on the basis of the observed failure modes and the relationships obtained from the experimental data, such as hysteretic curves, deformation curves, stiffness degradation curves, energy dissipation capacity, load curvature curves, and strain development curves. Experimental results showed that the failure mode of precast hybrid steel–concrete beams was different from that of precast concrete beams. The precast hybrid steel–concrete beam retained ductility comparable to that of precast concrete beams. Generally, the initial stiffness of precast hybrid steel–concrete beams was smaller than that of precast concrete beams, but the stiffness degradation was more stable. On the basis of measured crack propagation and failure mode, deformation curves, and the development of strain in steel beams and longitudinal reinforcements, the stress between the steel beam and concrete beam can be effectively transmitted to one another by the proposed connection form.